Effects of Specified Performance Criterion and Performance Feedback on Staff Behavior: A Component Analysis. (September 2014) - Hardesty, Samantha L.; Hagopian, Louis P.; McIvor, Melissa M.; Wagner, Leaora L.; Sigurdsson, Sigurdur O.; Bowman, Lynn G.
The present study isolated the effects of frequently used staff training intervention components to increase communication between direct care staff and clinicians working on an inpatient behavioral unit. Written "protocol review" quizzes developed by clinicians were designed to assess knowledge about a patient's behavioral protocols. Direct care staff completed these at the beginning of each day and evening shift. Clinicians were required to score and discuss these protocol reviews with direct care staff for at least 75% of shifts over a 2-week period. During baseline, only 21% of clinicians met this requirement. Completing and scoring of protocol reviews did not improve following additional in-service training ( M = 15%) or following an intervention aimed at decreasing response effort combined with prompting ( M = 28%). After implementing an intervention involving specified performance criterion and performance feedback, 86% of clinicians reached the established goal. Results of a component analysis suggested that the presentation of both the specified performance criterion and supporting contingencies was necessary to maintain acceptable levels of performance.